The role of regulatory T cells in respiratory infections and allergy and asthma - HIGGINS, SARAH; MILLS, KINGSTON (My University, 2010)
The role of distinct CD4+ T cell populations in regulating the nature and strength of immune responses is well documented, and in the past has principally focused on the cross regulation of Th1 and Th2 cells, which secrete IFN-? and IL-4 respectively. However, the identification of T cells capable of suppressing responses mediated by both Th1 and Th2 cells, termed regulatory T (Treg) cells, has prompted a paradigm shift in our understanding of the regulation of immune responses to infection and environmental antigens. This review will focus on the role of Treg cells in the lungs following infection with respiratory pathogens and will discuss the targeting of Treg cells in the development of new therapies for immune-mediated respiratory diseases, such as allergy and asthma.
PUBLISHED
PubMed ID: 20425510
Keywords: Immunology; Allergy; Asthma; Respiratory Infection; Regulatory T cell; Immunology, Inflammation & Infection